PROLEGOMENA TO BLENDED LEARNING: A NOVEL TOOL FOR DEVELOPING SELF DIRECTED LEARNING (SDL) AND THE 70-20-10 MODEL LEARNING FOR PHARMACY STUDENTS - PRAVEEN D; PALANI SHANMUGASUNDARAM; VIJEY AANANDHI M (International Journal of Pharma and Bio Sciences, 2016)
The present article discusses the preparatory steps of the faculty members for the implementation of blended learning. It challenges to think about the possibilities of blended learning implementation in Pharmaceutical education. Gen Z students are expected more information from online even from their own faculty members rather than spending much time in classroom environment The students are not interested in passive listening and doing class work in isolation. These challenges are prompting many colleges and universities to explore new approaches, especially blended learning, for delivering courses. Blended learning delivers higher levels of learning interactivity and collaboration. Blended learning leads to self-directed learning of the students as well as students’ skill will enhance the 70-20-10 learning frame work at the latter stage. This study also brings out the importance of Self Directed Learning (SDL) and the experience of 70-20-10 framework. Discussion is made on the various skills required for the blended learning, self-directed learning and skills which are to be imparted to the students of pharmacy.